Pengaruh Gaya Hidup, Brand Trust, Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Tokopedia - Muhammad Irfan Asmi; Muhammad Zaini (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
Company in Indonesia, Tokopedia offers a platform for consumers and sellers to do business online. This research was conducted to find out how lifestyle, brand trust, and service quality influence purchasing choices, purchasing decisions using a quantitative approach with a survey conducted using the Google Form. The research sample was selected as many as 100 respondents or an unknown population using the non-purposive sampling technique in the Leweshow formula. Methods of analysis of data testing using validity test, reliability test, classical assumption test, multiple linear regression test, and hypothesis testing are used to assess the research data collected. The results of this study are that lifestyle variables have a positive and significant effect on purchasing decisions then the brand trust variable has no positive and significant effect on purchasing decisions and the service quality variable has a positive and significant effect on purchasing decisions. In addition, based on the SPSS output results, lifestyle variables, brand trust, service quality have a significant simultaneous effect on purchasing decisions at Tokopedia in Samarinda City